REALITIES OF MODERN ART EDUCATION (ACCORDING TO THE RESULTS OF THE TEACHING COMMUNITY SURVEY) - Komarovska, Oksana (Theoretical and Methodical Problems of Children and Youth Education, 2022)
The issues of art education that have occurred and intensified in the last six months in connection with the large-scale of the Russian Federation’s aggression against Ukraine have been updated. The purpose of the article is to outline the state and prospects of art education for students in the progress of Ukraine towards the post-war reconstruction implemented by the author in the tasks of systematizing the results of the pedagogical community survey and the corresponding ranking of the problem in its perception. It has allowed us to define more clearly the methods of its psychological and pedagogical solution. The methods of fact-finding survey of respondents with further description of the obtained data, analysis of identified problems with the theoretical explanation of their essence and causes, determination of predicted ways of eliminating identified contradictions in art education of students during the survey were used. The process of the experimental survey is described. Systematization of the results is based on six blocks that reflect the need for a valuable rethinking of the content of art education, the difficulties of distance art learning for students, the teachers’ worries for the destruction of national heritage, objects of education and culture because of military actions and the organization of education in temporarily occupied territories. Moreover, psychological problems among children, their parents and teachers are growing. The deepening inferior attitude towards artistic disciplines against the background of military actions has caused to anxiety and specific methodical questions regarding the teaching of various types of art. During the analysis of the results of the experiment, the emphasis was placed on the first block of identified problems, the connection between the rethinking of values and the de-Russification of the content as well as the strengthening of the national content of the educational content, bringing to the fore the task of patriotic education through art. The key role of this value reflection in relation to the rest of the actualized issues, which consists of scientific novelty, is presented. The article is addressed to teachers of art and other disciplines of institutions of general secondary, higher art and art-pedagogical, out-of-school, specialized art education.